Examining pediatric care for newly immigrated families: Perspectives of health care providers. (28th May 2017) - Nicholas, David; Fleming-Carroll, Bonnie; Durrant, Michele; Hellmann, Jonathan
ABSTRACT: Respect for the ethnicity and cultural background of families are important components of health care delivery. However, the needs of new immigrants in pediatric care systems remain under-addressed in the literature. This study utilized a qualitative approach of interpretive description to elicit the pediatric health care experiences and needs of new immigrants to Canada, from the perspective of health care providers who worked extensively with newcomers. Two focus groups of multidisciplinary health care providers were conducted in a tertiary-level pediatric hospital. Results identify that the needs of new immigrant families are often insufficiently met by existing pediatric care practices. Needs include subsistence requirements such as income, transportation, and family understanding about the complex processes of health care in the new society. Newly immigrated families reportedly experience emotional adjustment and social support struggles and needs. Information and support to navigate the health care system are warranted. These formidable challenges invite proactive approaches, including navigation and resource finding supports as well as culturally responsive family-centered care.